Generation of an estrogen receptor beta‐iCre knock‐in mouse. Issue 1 (8th January 2016) - Cacioppo, Joseph A.; Koo, Yongbum; Lin, Po‐Ching Patrick; Osmulski, Sarah A.; Ko, Chunjoo D.; Ko, CheMyong
Summary: A novel knock‐in mouse that expresses codon‐improved Cre recombinase (iCre) under regulation of the estrogen receptor beta ( Esr2 ) promoter was developed for conditional deletion of genes and for the spatial and/or temporal localization of Esr2 expression. ESR2 is one of two classical nuclear estrogen receptors and displays a spatiotemporal expression pattern and functions that are different from the other estrogen receptor, ESR1. A cassette was constructed that contained iCre, a polyadenylation sequence, and a neomycin selection marker. This construct was used to insert iCre in front of the endogenous start codon of the Esr2 gene of a C57BL/6J embryonic stem cell line via homologous recombination. Resulting Esr2‐iCre mice were bred with ROSA26‐lacZ and Ai9‐RFP reporter mice to visualize cells of functional iCre expression. Strong expression was observed in the ovary, the pituitary, the interstitium of the testes, the head and tail but not body of the epididymis, skeletal muscle, the coagulation gland (anterior prostate), the lung, and the preputial gland. Additional diffuse or patchy expression was observed in the cerebrum, the hypothalamus, the heart, the adrenal gland, the colon, the bladder, and the pads of the paws. Overall, Esr2‐iCre mice will serve as a novel line for conditionally ablating genes in Esr2 ‐expressing tissues, identifying novel Esr2 ‐expressing cells, and differentiating the functions of ESR2 and ESR1. genesis 54:38–52, 2016. © 2016 Wiley Periodicals, Inc.